An Expanding World of Novel Psychoactive Substances: Opioids - Zawilska, Jolanta B. (Frontiers in Psychiatry, 2017)
The abuse of novel psychoactive substances (NPS) has been increasing dramatically worldwide since the late 2000s. By the end of 2015, more than 560 NPS had been reported to the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA). Although the most popular compounds are synthetic cannabinoids and psychostimulatory derivatives of cathinone (so-called β-keto-amphetamines), novel synthetic opioids have recently emerged on the recreational drug market. They include fentanyl (a potent narcotic analgesic) and its analogues (e.g., acetylfentanyl, acryloyfentanyl, carfentanil, -methylfentanyl, 3-methylfentanyl, furanylfentanyl, 4-fluorobutyrylfentanyl, 4-methoxybutyrylfentanyl, 4-chloroisobutyrylfentanyl, 4-fluoroisobutyrylfentanyl, tetrahydrofuranylfentanyl, cyclopentylfentanyl and octofentanil), and compounds with different chemical structures, such as AH-7921, MT-45 and U-47700. This survey provides an overview of the pharmacological properties, pattern of use, desired and unwanted effects of the above listed novel opioids. Special emphasis is given to cases of non-fatal and lethal intoxication involving these compounds.